IMPLEMENTASI SENTRA MAIN PERAN DALAM PENGEMBANGAN KECERDASAN VERBAL LINGUISTIK DAN INTERPERSONAL ANAK (Studi Kasus di TK Aisyiyah Nur’aini Ngampilan Yogyakarta) - Nia Kurniasari (QURROTI, 2020)
Communication skills are needed for early childhood as a provision in social interaction which includes language skills and socialization. Verbal linguistic and interpersonal intelligence of children is needed in social life. This intelligence stimulation can be done through directed play in dramatic play. The objectives of this study are to know the implementation of the dramatic play in TK Aisyiyah Nuraini, and to know the development of children's linguistic and interpersonal verbal intelligence. This research method is qualitative field research with a case study approach. The technique of collecting data uses in depth interviewing which is reinforced by observation and documentation data. The results showed that first, the implementation of the BCCT method in Tepadu Aisyiyyah PAUD Yogyakara Performance was carried out in an integrated manner starting from the time of welcoming the child to the closing activity. Second, the development of verbal linguistic intelligence and children's interpersonal intelligence arises in the role play center through literacy support, social playing experiences, playing macro and micro roles, extensive playing opportunities, social interaction and communication between peers and with teachers. The results of observations on the development of verbal linguistic and interpersonal intelligence of children based on indicators obtained results that are developing as expected. It can be concluded that the dramatic play can develop verbal linguistic and interpersonal intelligence of children by providing consistent (continuous) and effective stimulation.